DEVELOPMENT OF HOTS-BASED FUNCTION DERIVATIVE WORKSHEET THROUGH A NETWORK LEARNING SYSTEM SPADA - Sri Satriani; Wahyuddin Wahyuddin; Andi Aliem Syahri (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to develop a valid, effective, and practical HOTS-based worksheet for calculus courses in the Mathematics Education Department. The development of the worksheet is expected to improve critical and creative thinking skills, which is implemented through the Online Learning System (SPADA). This research is development research with the research subject being 27 students of Mathematics Education, Muhammadiyah University of Makassar. The instruments used in this study were instrument validation sheets, test, and student response questionnaires. This worksheet development process is adapted from the model of development of the 4-D models, which consists of define, design, develop, and disseminate. The results of the validation assessment were an average score of 3.61 in the valid categories. The result of the lecturers' practicality at 3.6 with the practical category. Furthermore, the results of the effectiveness assessment through the HOTS test showed that the percentage of classical completeness was 86.7%. The students' responses showed a positive response to this worksheet. The assessment results showed that the average pretest was 46.85, while the postest was 74.81. There is an increase in the average value of higher-order thinking skills from pretest to postest in field trials. So it produces worksheets based on HOTS through SPADA that have met the valid, practical, and effective aspects and can facilitate students in practicing their higher-order thinking skills.